2019
DOI: 10.1103/physrevd.100.024019
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing in Weyl gravity

Abstract: We calculate the deflection angle of light from a distant source by a galaxy cluster in Weyl's conformal gravity. The general method of calculation is first applied to calculate the deflection angle in Schwarzschild-de Sitter (Kottler) spacetime. The deflection angle calculated in Kottler spacetime includes the contribution of the cosmological constant, which quantitatively agrees with one work and disagrees with many works in the literature. We then calculate the deflection angle in Mannheim-Kazanas spacetime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 96 publications
(251 reference statements)
0
15
0
Order By: Relevance
“…The astrophysical relevance of this solution was further confirmed in a number of works [28][29][30]. This black hole solution [24] has been recently studied in a number of papers, with the emphasis to lensing and particle motion [31][32][33][34][35][36][37], thermodynamics [38,39] and quasinormal modes [40][41][42][43].…”
Section: Introductionmentioning
confidence: 69%
“…The astrophysical relevance of this solution was further confirmed in a number of works [28][29][30]. This black hole solution [24] has been recently studied in a number of papers, with the emphasis to lensing and particle motion [31][32][33][34][35][36][37], thermodynamics [38,39] and quasinormal modes [40][41][42][43].…”
Section: Introductionmentioning
confidence: 69%
“…[100,101] also address observed galaxy cluster motion with no dark matter. Furthermore, if CG is to account for all dark matter in the Universe, it is so far unclear if it can pass gravitational lensing tests [102][103][104][105][106][107][108], and inconsistencies with gravitational wave observation of binaries have been found [109]. Also, tensions between predictions of primordial nucleosynthesis in a CG cosmology and observation of light element abundances have been found in refs.…”
Section: Conformal Gravity Cosmologymentioning
confidence: 99%
“…Since conformal Weyl gravity has been revisited by Mannheim and Kazansas (1989) [5], several authors in recent times have obtained expressions for deflection of light and performed lensing analysis in conformal gravity in Mannheim-Kazansas space-times (e.g., [22][23][24][25][26][27][28][29]), particularly in the context of weak lensing scenario. But the bending angle expressions given by the different authors are found different and non-convergent.…”
Section: Introductionmentioning
confidence: 99%